Insulin induction instigates cell proliferation and metastasis in human colorectal cancer cells - Lu, Chi-Cheng; Chu, Pei-Yi; Hsia, Shih-Min; Wu, Chi-Hao; Tung, Yu-Tang; Yen, Gow-Chin (International journal of oncology, 2017)
The progression of colorectal cancer has been reported to have a positive correlation with the combination of hyperglycemia and hyperinsulinemia in diabetic patients, leading to a lower survival rate. However, how insulin acts on colorectal cancer remains not well understood. The purpose of this study was to explore the effect of insulin on colon cancer cell proliferation and its underlying molecular signaling as well as the impact of insulin-induced in vitro metastasis. Our results showed that insulin markedly promoted cell proliferation, migration and anchorage-independent growth in human colon cancer HCT-116 cells. Insulin‑regulated insulin receptors (IRs) stimulate insulin receptor substrate 1 (IRS-1) and interact with the downstream signals, causing a rise in HCT-116 cell proliferation. Moreover, insulin significantly induced the migration ability of HCT-116 cells. The metastatic ability of matrix metalloproteinase-2 (MMP-2) mRNA and activity was activated by insulin. Overall, insulin-triggered cell proliferation and metastatic effects on colorectal cancer cells are mediated by IRS-1 and downstream molecules and by increasing phosphoinositide 3-kinase (PI3K)/Akt and mitogen-activated protein kinase (MAPK) signaling. Therefore, insulin induction might have the potential to induce colorectal cancer progression in diabetes patients.